The Political Economy of Social Exclusion with Implications for Immigration Policy - Mark Gradstein; Maurice Schiff (Institute for the Study of Labor (IZA), 2004)
Minorities, such as ethnic and immigration groups, have often been subject to exclusion through labor market discrimination, residential and employment segregation policies, business ownership regulations, restrictions on political participation, access to public services and more. This paper studies the dynamics of minority exclusion. From the viewpoint of the dominant majority, the exclusion decision balances the motive to redistribute income in its favor and the interest in avoiding potential civic unrest or even violent confrontation with the minority by allowing inclusion of some of its members. The analysis also has implications for immigration policies which have to take this group dynamics into account.
Keywords: I20; H41; D74; J61; 330; social exclusion; dynamics; immigration policy; Ethnische Gruppe; Soziale Isolation; Minderheitenpolitik; Migrationspolitik; Public Choice; Theorie